PELAKSANAAN PERJANJIAN KEMITRAAN ANTARA PERUSAHAAN PENGANGKUTAN DENGAN KURIR (Studi Kasus Perjanjian Kemitraan N0.230/PM/MAS/III/2022) - Siti Alfiatul Mukaromah; Maryati Bachtiar; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
This study discusses the cooperation agreement between the transportcompany and the courier (case study of the cooperation agreement No.230/PM/MAS/III/2022)”. An agreement is an act whereby one or more personsbind themselves to one or more other persons. Based on Article 1338 of the CivilCode which reads: "All legal agreements are law for those who make them".These agreements may not be revoked except with the consent of both parties, orfor reasons sufficient by law. The purpose of writing this thesis is; First, to findout the fulfillment of the transport company's rights and obligations with thecourier in the cooperation agreement on the basis of good faith; Second, seekefforts to resolve disputes about the rights and obligations of the carrier with thecarrier in a cooperation principle of good faith. The type of legal research theauthor uses is normative legal research or library law research.This type of research can be classified into the sociological researchtype because in this research the author conducts research directly at theresearch site or place to get a complete and clear picture of the problem underinvestigation. This survey was conducted by PT Satria Antaran Prima (SAP)Pekanbaru City, while the population and sample are all parties related to theissues examined in this survey, the data sources used, primary data and secondarydata, and tertiary data, data collection techniques in this study throughobservation and interviews.From the results of this research, the author concludes that the legalprotection of the rights and obligations of carriers with couriers based oncooperation agreements has not been fully implemented properly. The content ofthe cooperation agreement is determined unilaterally in relation to the carrier'sobligations. Couriers do not have the right to convey considerations about thecooperation agreement so that it is less profitable for the parties, especially thecourier. So that the rights and obligations under the partnership agreement arenot met. Settlement of disputes about the rights and obligations of the carrier withthe carrier in the first cooperation agreement through consultation and thesecond through mediation. Dispute settlement through consultation has notachieved the maximum result in practice, so that the parties to the dispute havenot been given proportionate rights and obligations.Keywords: Courier, Transport company, Cooperation agreement.